The effect of modified alternate day calorie restriction on non-alcoholic fatty liver disease (NAFLD) - Yusoff, Khairiah Mat (2018)
Introduction: NAFLD is a serious medical issue worldwide. Various diet modifications had been implemented to improve liver steatosis. SWE is an emerging technique that offers non-invasive method of liver steatosis assessment. In this study, we aimed to compare the liver steatosis grading and liver elasticity among NAFLD patients who underwent 8 weeks of MADCR. Methodology: Using the Aixplorer® ultrasound, liver ultrasound of 39 subjects (32 interventional and 9 control subjects) were performed. Liver steatosis grading, fibrosis grading and shear wave elastography of all patients were acquired. Liver steatosis and liver elasticity level pre and post pre intervention were compared. Correlation of the liver steatosis and gradings were analysed using Kendall b tau analysis. Results: The mean liver steatosis grade and fibrosis level of the 30 participants in the intervention group were significantly reduced after MADCR (modified alternate day calorie restriction) programme. Our result showed that 10 patients had improved liver steatosis grading, whereby 8 patients improve from grade 2 to grade 1 and 2 patients from grade 1 to grade 0. Our study showed significant mean difference of liver elasticity in intervention group after MADCR (p value <0.001). From the analysis of the readings from all the participants (n=78), the SWE values showed significant weak correlation with the steatosis grading (0-3) of the fatty liver (P value 0.013). Conclusions: MADCR is beneficial to improve liver steatosis. SWE is a useful and reliable method to assess liver elasticity after intervention.